nclusion And Reciprocal Styles and Their Effect On Learning Layup In Basketball - Mufeed, Raya; Mohammed, Ismael (Journal of Physical Education, 2017)
e best teaching style if the one that include the learners' abilities, readiness and potentials thus the researchers combined two teaching styles; inclusion and reciprocal teaching styles to teach layup in basketball for students. The research aimed at identifying the effect of combining two teaching strategies; inclusion and reciprocal style in teaching layup in basketball for second grade secondary school students. The researchers hypothesized statistical differences between pre and posttests using both strategies. The subjects were (20) students. The results showed great development in learning layup in basketball. Finally the researchers recommended combining inclusion and reciprocal teaching styles in teaching layup in basketball